Pengaruh Media Pembelajaran dan Pengelolaan Kelas terhadap Prestasi Belajar Siswa di SMK Negeri Kecamatan Tanete Riattang, Kabupaten Bone - Suprianto Suprianto; Sitti Hardiyanti Arhas; Rudi Salam (Jurnal Ad'ministrare, 2018)
The objectives research are, (i) whether there is influence of utilizing learning media toward students learning  achievement in Office Administration program at SMKN in Tanete Riattang subdistrict of Bone district; (ii) whether there is influence of clasrooms management toward students learning  achievement in Office Administration program at SMKN in Tanete Riattang subdistrict of Bone district. (iii) whether there is influence collectivity of utilizing learning media and class management toward students learning  achievement in Office Administration program at SMKN (Public Vocational Schools) in Tanete Riattang subdistrict of Bone district. The research employed quantitative method. Data is collected through observation, questionnaire and documentation techniques. Data is analyzed by employing descriptive statistic and inferential statistic analysis., there is significant positive influence of  learning media towards the students learning achievement by 17%, there is significant positive influence classroom management toward the student learning achievement by 19,9%. The results of the research reveal that: there are significant positive influence between learning media and class management toward the students learning by 23,6%.